Wycena w warunkach rachunkowości zabezpieczeń - Iwuć, Katarzyna (Valuation in Hedge Accounting Conditions, 2007)
Every company which operates in a risk environment and uses hedging for risk elimination purposes has the opportunity to apply special accounting rules called hedge accounting. Decision: to use or not to use hedge accounting is important because of its influence on the financial statement. Hedge accounting provides a lot of deviation from the general accounting approach, one of them is special valuation of the hedged position and hedging instrument. While using hedge accounting the companies have the opportunity to override the standard accounting rules which oblige them to valuate certain position at historical cost. This special rules which are distinctive only for a hedge accounting help to avoid much of the volatility in the financial statement which would occur when the derivative and hedge position were recognized as required by normal accounting principles. The article describes how hedge accounting changes the picture of hedging in the financial statement.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 212-221